An MPF Based Aerial Platform Tracking Method for Road Network Targets - Yuan, Jing; Chen, Xin; Zhang, Min; Zhang, Pengfei (Journal of physics. Conference series, 2022)
This paper presents a new algorithm to improve the tracking accuracy of the aerial mobile observation platform by using road information constraints. Combined with the road information and Mixed Particle Filter(MPF) algorithm, the Road Constrained Mixed Particle Filter(RCMPF) algorithm is proposed. RCMPF algorithm can effectively solve the problem of non-linear observation equation of aerial observation platform and realize the tracking of ground targets. The simulation results show that the algorithm improves the tracking accuracy of the target.